2022
DOI: 10.1002/ghg.2191
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric removal of methane by enhancing the natural hydroxyl radical sink

Abstract: According to the latest report from the intergovernmental panel on climate change (IPCC), currently, global warming due to methane (CH4) alone is about 0.5°C while due to carbon dioxide (CO2) alone is about 0.75°C. As CH4 emissions will continue growing, in order to limit warming to 1.5˚C, some of the most effective strategies are rapidly reducing CH4 emissions and developing large scale CH4 removal methods. The aim of this review article is to summarise and propose possible methods for atmospheric CH4 removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…However, the known pathways for CH 4 production related to ROS, such as those involving Bacillus subtilis and Escherichia coli, are not dominant in desert ecosystems 54 . In addition, •OH is the largest sink for CH 4 , and around 80-90% of global methane is absorbed through oxidation by •OH, while the oxidation of methane by methanotrophic bacteria accounts for less than 10% of methane consumption 55 . The limited microbial source of CH 4 may be rapidly absorbed by •OH.…”
Section: Discussionmentioning
confidence: 99%
“…However, the known pathways for CH 4 production related to ROS, such as those involving Bacillus subtilis and Escherichia coli, are not dominant in desert ecosystems 54 . In addition, •OH is the largest sink for CH 4 , and around 80-90% of global methane is absorbed through oxidation by •OH, while the oxidation of methane by methanotrophic bacteria accounts for less than 10% of methane consumption 55 . The limited microbial source of CH 4 may be rapidly absorbed by •OH.…”
Section: Discussionmentioning
confidence: 99%
“…Some CH 4 oxidation approaches, such as atmospheric hydroxyl radical enhancement, would target gases in different ratios. The majority of atmospheric hydroxyl radicals oxidize CO molecules, so we also consider an approach in which CO and CH 4 are destroyed at the same rates seen in the bulk atmosphere (5 tons of CO per ton of CH 4 , table 1) [12]. This approach (A3) results in ∼36% more cooling than negative emissions by 2100 (figure 1).…”
Section: Atmospheric Removal Approachesmentioning
confidence: 99%
“…Another study demonstrated oxidation of 2 ppm CH 4 at ambient temperature through photolysis of chlorine gas into chlorine radicals (t R,99% = ∼350 s) [24]. Other proposals to generate radicals in ways that mimic methane's natural oxidation process include chlorine radicals through iron salt aerosols [25] and hydroxyl radicals through ozone photolysis [23,26,27].…”
Section: State-of-the-art Methane Oxidation Technologiesmentioning
confidence: 99%